The influence of financial performance and governance on non-financial performance disclosures - Nugrahani, Tri Siwi; Firdaus, Taslim; Sari, Ratna Purnama (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research aims to examine the influence of financial performance and corporate governance on non-financial performance, i.e., the disclosure of the sustainability report (SR).Design/Methodology/Approach: This research used a sample of 35 industrial companies listed on the IDX during 2017-2022 and prepared annual reports (AR) and SR. The total observation data was 210 companies. The data analysis technique employed multiple regression and hypothesis testing using the t-test, with a significance of 5%.Research findings: The research results demonstrated that governance, including the independent board of commissioners and audit committee, exerted a positive effect on SR disclosure. However, the board of directors, institutional share ownership, public share ownership, and ROA did not affect SR disclosure.Theoretical contribution/ Originality: Theoretically, this research contributes to the fact that the agency theory approach can be used to determine SR disclosure.Practitioner/Policy implication: By optimizing independent boards of commissioners and audit committees, companies can help companies supervise managers, thereby increasing SR disclosure.Research limitation/Implication: This research was limited to examining governance on the board of directors, independent board of commissioners, audit committee, and institutional and public share ownership. The authors have not tested other governance, such as managerial ownership and remuneration committees, so numerous additional factors remain that can impact SR disclosure.